2011
DOI: 10.5007/2175-7925.2011v24n1p37
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação de Ctenogobius shufeldti (Jordan e Eigenmann, 1887) (Teleostei, Gobiidae) na Baía de Guaratuba, Atlântico oeste subtropical doi:10.5007/2175-7925.2011v24n1p37

Abstract: ResumoA dieta do teleósteo Ctenogobius shufeldti foi estudada na Baía de Guaratuba, litoral sul do Brasil, objetivando descrever variações espaço-temporais e compreender a participação dessa espécie criptobêntica na teia tró¿ ca da comunidade deste sistema estuarino. Foram analisados 397 espécimes (comprimento total de 21 a 70mm) em 12 meses de amostragem junto à vegetação marginal da região mais interna da Baía e porção ¿ nal de dois rios aÀ uentes. O conteúdo estomacal foi identi¿ cado e os dados foram trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
3
0
2
Order By: Relevance
“…These results described C. shufeldti in the Paranaguá Bay estuarine complex as typical generalized, omnivorous benthic feeders, exhibiting a broad feeding niche. These results are consistent with those of Zanlorenzi & Chaves (2011), who described the same food categories as the most important ones in the Guaratuba Bay estuary (just south of Paranaguá Bay). Results of this study are also partially in agreement with those of Corrêa & Uieda (2007), who identified ostracods and tanaids as the main prey in the Rio da Fazenda Estuary (northern coast of São Paulo).…”
Section: Discussionsupporting
confidence: 92%
“…These results described C. shufeldti in the Paranaguá Bay estuarine complex as typical generalized, omnivorous benthic feeders, exhibiting a broad feeding niche. These results are consistent with those of Zanlorenzi & Chaves (2011), who described the same food categories as the most important ones in the Guaratuba Bay estuary (just south of Paranaguá Bay). Results of this study are also partially in agreement with those of Corrêa & Uieda (2007), who identified ostracods and tanaids as the main prey in the Rio da Fazenda Estuary (northern coast of São Paulo).…”
Section: Discussionsupporting
confidence: 92%
“…(); 3, Sergipense et al. (); 4, Froese & Pauly (); 5, Zanlorenzi & Chaves (); 6, Chaves & Vendel (); 7, Guedes et al. (); 8, Vasconcelos Filho et al.…”
Section: Resultsmentioning
confidence: 99%
“…These items were the smallest found in all guts, therefore proportionally more appropriate to the mouth size of juveniles. Furthermore, these items are preyed by other small cryptic fish in Guaratuba Bay, such as Ctenogobius shufeldti , which diet is based on ostracods (Zanlorenzi & Chaves, ). In tide pools, juveniles of diverse cryptic species also fed on ostracods and other small crustaceans (Pimentel et al, ).…”
Section: Discussionmentioning
confidence: 99%